REFLECTIONS ON THE REPERTORY IN MUSIC EDUCATION: FILLING THE GAP WITH CONTEMPORARY MUSIC - Érica Dias Gomes (Editora da Universidade de Santa Cruz do Sul, 2014)
Formal musical education in Brasil has been focusing common practice period repertory on all education segments. This research aims to reflect about this gap on musical education's repertory, especially regarding contemporary music. Therefore, theoretical review was carried out in order to present some facts on music education's history that have contributed to this repertory consolidation. Finally some notes about both contemporary music and life are exposed as argument for the importance of discussing these relations at school. Lastly this paper defends contemporary music as a significant issue for the purpose of develops musicality and relates students' everyday life to music education.